27 Increasing prescription of opioid analgesics and neuropathic pain medicines for spinal pain in australia. (20th August 2018) - Mathieson, Stephanie; Valenti, Lisa; Maher, Christopher; Britt, Helena; Li, Qiang; McLachlan, Andrew; Lin, Christine
Abstract : Objectives: Limited evidence exists on secular trends of analgesic medicines for spinal pain. We investigated general practitioner's (GP) recommendations of analgesic medicines for spinal pain and investigated characteristics associated with their recommendation. Method: We accessed data on spinal pain consultations from the Bettering the Evaluation and Care of Health (BEACH) database, a nationally representative database on GP activity in Australia. Data extracted included consultation details and management provided. Medicines recommended were grouped as simple analgesics, non-steroidal anti-inflammatory drugs (NSAIDs), opioid analgesics or neuropathic pain medicines. Multivariate logistic regression determined if patient characteristics and GP characteristics were associated with medication recommendations. Results: We analysed BEACH data for 9100 GPs who managed 39 303 patients with spinal pain between 2004 and 2014. Over the decade, analgesic recommendations increased. After accounting for patient and GP characteristics, there was a significant increase in the rate single-ingredient opioid analgesics (e.g. oxycodone) [annual relative increase of 6% (Rate Ratio (RR) 1.06 (95% CI 1.05 to 1.07)] and neuropathic pain medicines (e.g. pregabalin) [annual relative increase of 19% (RR 1.19 (95% CI 1.16 to 1.22)] were recommended; and a significant decrease in the rate NSAIDs were recommended [annual relative decrease of 4% (RR 0.96 (95% CI 0.95 to 0.97)]. Logistic regression identified several patient and GP characteristics associated with medicine recommendations, e.g. stronger opioids were less likely recommended for Indigenous patients [Odds Ratio 0.15 (95% CI 0.04 to 0.56)]. Conclusions: GP's analgesic recommendations for spinal pain have become increasingly divergent from guideline recommendations over time.